2018
DOI: 10.3389/fphys.2018.01670
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction-Associated Arrhythmogenic Substrates in Diabetes Mellitus

Abstract: There is increasing evidence that diabetic cardiomyopathy increases the risk of cardiac arrhythmia and sudden cardiac death. While the detailed mechanisms remain incompletely understood, the loss of mitochondrial function, which is often observed in the heart of patients with diabetes, has emerged as a key contributor to the arrhythmogenic substrates. In this mini review, the pathophysiology of mitochondrial dysfunction in diabetes mellitus is explored in detail, followed by descriptions of several mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 136 publications
(166 reference statements)
0
9
0
1
Order By: Relevance
“…Clinical data have demonstrated that there is a bidirectional relationship between diabetes mellitus and cardiovascular diseases, as well as heart failure ( Song et al, 2018 ). Various factors associated with diabetes mellitus, such as impaired calcium homeostasis, altered free fatty acid metabolism, an unbalanced redox state, and increased advanced glycation end products, contribute to cardiovascular complications ( Riehle and Bauersachs, 2018 ; Zhang et al, 2018 ; Zheng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data have demonstrated that there is a bidirectional relationship between diabetes mellitus and cardiovascular diseases, as well as heart failure ( Song et al, 2018 ). Various factors associated with diabetes mellitus, such as impaired calcium homeostasis, altered free fatty acid metabolism, an unbalanced redox state, and increased advanced glycation end products, contribute to cardiovascular complications ( Riehle and Bauersachs, 2018 ; Zhang et al, 2018 ; Zheng et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a great need to develop new anti-diabetic treatments and modify the existing therapeutic approaches (Sowton et al, 2019) in order to attenuate the complications of diabetes, especially microvascular complications (retinopathy, nephropathy, and neuropathy), macrovascular complications (ischemic heart disease, stroke, and peripheral vascular disease), and the diminished quality of life (Heusch, 2018;Karwi et al, 2018). Clinical data have demonstrated that there is a bidirectional relationship between diabetes mellitus and cardiovascular diseases, as well as heart failure (Song et al, 2018). Various factors associated with diabetes mellitus, such as impaired calcium homeostasis, altered free fatty acid metabolism, an unbalanced redox state, and increased advanced glycation end products, contribute to cardiovascular complications (Riehle and Bauersachs, 2018;Zhang et al, 2018;Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria influence cellular physiology in a variety of ways (41), and are involved in many pathologies, including epilepsy (152,153), thyroid function (154), cancer (155)(156)(157)(158), diabetes (159,160), and BrS (41), among others. Mitochondria produce adenosine triphosphate (ATP), which is required for protein phosphorylation, a process that is required for normal protein function (161).…”
Section: Mitochondria and Brugada Syndromementioning
confidence: 99%
“…In diabetes, mitochondria increase the production of reactive oxygen species (ROS), thus causing oxidative stress and tissue damage (21). Mitochondrial damage may even precede hyperglycemia in diabetes (28). These data suggest that mitochondrial dysfunction may be a common pathway of diabetes and I/R injury severity.…”
Section: Introductionmentioning
confidence: 99%